Taxonomic composition and monophyly of the genus Magnificus (Lepidoptera: Hepialoidea: Hepialidae) - Grehan, John R.; Mielke, Carlos G.c.; Minet, Joël; Ignatev, Nikolai; Buchsbaum, Ulf; Xue, Dayong (Zootaxa, 2021)
The genus Magnificus Yan, 2000 was originally established to include M. jiuzhiensis Yan, 2000 and M. zhiduoensis Yan, 2000. Here we also include the species M. bouvieri (Oberthür, 1913) comb. n., M. dirschi (Bang-Haas, 1939) comb. n., M. miniatus (Chu & Wang, 1985a) comb. n., M. regius (Staudinger, 1896) comb. n., and M. roseus (Oberthür, 1911) comb. n. Monophyly of Magnificus is supported by the shared presence of a unique shape of the tergosternal sclerite in the anterio-abdominal region and pseudoteguminal arm in the male genitalia. We also provide evidence for the inclusion of Magnificus and the northern Eurasian genera Hepialus Fabricius, Pharmacis Hübner, Triodia Hübner and Zenophassus Tindale as members of a larger monophyletic group supported by the shared presence in the male genitalia of a deep U-shaped medial notch in the posterior margin of the saccus and an expanded triangular flange at the lateral corners of the notch. The reciprocally allopatric distribution of Magnificus and its probable sister group is consistent with each originating locally by vicariance over different parts of a widespread ancestral range. This divergence may be the result of tectonic uplift in central Asia.